Chronic pain in a patient with Ehlers-Danlos syndrome (hypermobility type): The role of myofascial trigger point injections. Issue 1 (January 2017) - Tewari, Saipriya; Madabushi, Rajashree; Agarwal, Anil; Gautam, Sujeet K.; Khuba, Sandeep
Summary: Chronic widespread musculoskeletal pain is a cardinal symptom in hypermobility type of Ehler Danlos Syndrome (EDS type III). The management of pain in EDS, however, has not been studied in depth. A 30 year old female, known case of EDS, presented to the pain clinic with complaints of severe upper back pain for 6 months. Physical examination of the back revealed two myofascial trigger points over the left rhomboids and the left erector spinae. Local anaesthetic trigger point injections were given at these points, followed by stretching exercises under analgesic cover for the first week. After 1 week the patient reported 60–80% pain relief. This case highlights that we must keep a high index of suspicion for the more treatable causes of pain like myofascial pain syndrome in patients suffering from EDS, and should address it promptly and appropriately in order to maximise patient comfort.